The other-race effect in the uncanny valley. Issue 166 (October 2022) - Saneyoshi, Ayako; Okubo, Matia; Suzuki, Hikaru; Oyama, Takato; Laeng, Bruno
Highlights: We examined whether the other-race bias modulates the uncanny valley phenomenon. The participants rated the CG faces of their own race more unpleasant. Pupillary diameters were recorded as an objective measure of affective responses. Pupil dilations showed the different reflection in Japanese and Norwegian. To create acceptable robots, a clearly different appearance is desirable. Abstract: The uncanny valley stands for the feeling of eeriness triggered by something that looks almost, but not exactly, like a real human. This study, thus, examined whether other-race bias modulates the uncanny valley phenomenon; both effects are based on familiarity with different face categories. We asked participants from Japan and Norway to rate the unpleasantness of computer-generated East Asian and European faces with progressively scaled eye sizes (from unnaturally small to unnaturally large). Simultaneously, we monitored their pupil sizes with an eye tracker. Pupillary diameter can be used as an objective measure of the uncanny feeling elicited by faces. We found that even when the changes in the images eye size were small, both Japanese and Norwegian participants rated the faces of their own race as more unpleasant than the faces of the different races, indicating the presence of other-race bias in the context of the uncanny valley, at least with computer-generated faces. Similar to the rating data, the pupils of Japanese participants dilated more for East Asian faces than for European faces. In contrast, the pupils of Norwegian participants dilated more for East Asian faces than for European faces. These differences can be attributed to unequal exposure to the faces from different races within each culture, thus, demonstrating other-race bias in the uncanny valley.